Conditioning Factors of Heat Tolerance - Joana Guedes (2011)
To dwell in hot thermal environments is common in several types of economic activities and carries consequences to the exposed persons' health. Opposed to extreme cold thermal environments, which create situations that can be solved resorting to personal protective measures, extreme hot environments, in a general manner, can only be avoided through collective protection measures. When besides dwelling, there is need of physical activity, health risks are seriously jeopardized. This paper intends to chart the scientific evolution that is able to respond to the questions related to tolerance in hot environments, in an integrated way to allow unstudied areas to be identified. It also intends to gather information regarding tendencies, exposure limit values determination and validation. Bibliography research was carried out using a set of keywords previously defined. The results were grouped and only relevant papers and of high scientific rigor were selected. Individual factors have significant influence in heat tolerance. From research it can determined that: advanced age, reduced aerobic capacity, high quantity of adipose tissue, low body mass women, malnutrition and substance abuse, chronic illness and diseases in general contribute to reduce heat tolerance capacity.